Free gracilis flap for chest wall reconstruction in male patient with Poland syndrome after implant failure - Mario Cherubino; Francesca Maggiulli; Igor Pellegatta; Luigi Valdatta (Indian Journal of Plastic Surgery)
Poland’s syndrome (PS) is a congenital monolateral deformity that may involve breast, chest wall, and upper limb with different degrees of clinical expressions. In some cases, the problem is mainly cosmetic, and the reconstruction should be performed to achieve minimal scarring and donor site morbidity. The authors describe a case report of a male patient with PS who developed a severe capsular contraction after 25 years implant reconstruction, who was treated after explantation using free gracilis flap (FGF). In this patient, only the pectoralis major muscle was missing. An FGF was performed to reconstruct the anterior axillary fold and the soft tissue defect. There was no flap loss, the patient had a clearly improved appearance of the chest wall, and the pain syndrome was solved. In this case report, we demonstrate our experience with the use of an FGF for chest wall reconstruction in male patients with PS after prosthesis explantation.